All Days 2013
DOI: 10.2523/iptc-16697-ms
|View full text |Cite
|
Sign up to set email alerts
|

The First Subsea Completion by an Operator in KN Field, Offshore Malaysia

Abstract: The KN field in KM cluster is located approximately 200km offshore, at water depths ranging from 59–102m. The field is part of the KM Cluster Integrated Development Plan, where the primary objective for KN field development is to recover the reserve from fringing pinnacle reef carbonate reservoir, expected to be achieved through two deviated 7-inch open-hole monobore subsea wells. KN field is expected to deliver around 200 to 300 MMSCF/day to the LNG plant to help relieve an anticipated gas shortage, as such f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The results of the MRT measurements on well SS-1 are shown in Table 6 [Mahadi et al, 2013]. The test results confirmed that both wells could produce over 150 MMscfd of gas, giving a total production rate potential of greater than 300…”
Section: Figure 2 -Well Ss-1 Gas Condensate and Water Flow Rates Durmentioning
confidence: 68%
See 3 more Smart Citations
“…The results of the MRT measurements on well SS-1 are shown in Table 6 [Mahadi et al, 2013]. The test results confirmed that both wells could produce over 150 MMscfd of gas, giving a total production rate potential of greater than 300…”
Section: Figure 2 -Well Ss-1 Gas Condensate and Water Flow Rates Durmentioning
confidence: 68%
“…The aim was to achieve a production rate of 60 MMscfd within 2 hours, increasing to 100 MMscfd within 4 hours [Mahadi et al, 2013]. OLGA multiphase flow transient simulations predicted that full well clean-up would be achieved within 6 hours from start-up prior to conducting well deliverability tests.…”
Section: Well Clean-up and Testingmentioning
confidence: 99%
See 2 more Smart Citations